Taxonomic review of Korean Drunella Needham (Ephemeroptera: Ephemerellidae), with description of Drunella koreana sp. nov. - Shin, Sang Kyu; Bae, Yeon Jae (Zootaxa, 2026)
Larvae of the genus Drunella Needham, 1905 exhibit intraspecific morphological variation, which has complicated species delimitation—particularly within the Drunella ishiyamana species complex in Northeast Asia. In this study, all five Korean Drunella species were comprehensively reviewed. Phylogenetic analysis based on mitochondrial COI gene sequences revealed significant genetic divergence between Korean and Japanese D. ishiyamana complex specimens. Korean specimens also differ morphologically, particularly in the shape and size of head horns and abdominal tubercles. These differences support the designation of the Korean population as a new species, Drunella koreana sp. nov. An updated identification key to the Korean Drunella species is provided. The relatively high genetic diversity within the Northeast Asian D. ishiyamana complex is also discussed.